Answer:
(a + b) = 8x +4
(a - b) = -2x +16
(a * b) =
![15x^(2)+32x-60](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5azsmtd0ka1qzfswa7lciyb6h7cttj4uoz.png)
Explanation:
We have been given the functions;
a(x) = 3x + 10 and b(x) = 5x − 6
Part A:
(a + b) = a(x) + b(x) # we simply add the two given functions
(a + b) = 3x + 10 + 5x − 6
(a + b) = 8x + 4
Part B:
(a - b) = a(x) - b(x) # we simply subtract the two given functions
(a - b) = (3x + 10 ) - (5x − 6)
(a - b) = 3x + 10 -5x +6
(a - b) = -2x + 16
Part C:
(a * b) = a(x)*b(x)
# we simply find the product of the two given functions
(a * b) = (3x + 10)*(5x − 6)
(a * b) =
![15x^(2)-18x+50x-60=15x^(2)+32x-60](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8ebk6ufq5g0990dl2sdtfeydyb6u5oot6z.png)